Quantitative SARS-CoV-2 anti-spike responses to Pfizer–BioNTech and Oxford–AstraZeneca vaccines by previous infection status. (October 2021) - Eyre, David W.; Lumley, Sheila F.; Wei, Jia; Cox, Stuart; James, Tim; Justice, Anita; Jesuthasan, Gerald; O'Donnell, Denise; Howarth, Alison; Hatch, Stephanie B.; Marsden, Brian D.; Jones, E. Yvonne; et al.
Abstract: Objectives: We investigated determinants of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) anti-spike IgG responses in healthcare workers (HCWs) following one or two doses of Pfizer–BioNTech or Oxford–AstraZeneca vaccines. Methods: HCWs participating in regular SARS-CoV-2 PCR and antibody testing were invited for serological testing prior to first and second vaccination, and 4 weeks post-vaccination if receiving a 12-week dosing interval. Quantitative post-vaccination anti-spike antibody responses were measured using the Abbott SARS-CoV-2 IgG II Quant assay (detection threshold: ≥50 AU/mL). We used multivariable logistic regression to identify predictors of seropositivity and generalized additive models to track antibody responses over time. Results: 3570/3610 HCWs (98.9%) were seropositive >14 days post first vaccination and prior to second vaccination: 2706/2720 (99.5%) were seropositive after the Pfizer–BioNTech and 864/890 (97.1%) following the Oxford–AstraZeneca vaccines. Previously infected and younger HCWs were more likely to test seropositive post first vaccination, with no evidence of differences by sex or ethnicity. All 470 HCWs tested >14 days after the second vaccination were seropositive. Quantitative antibody responses were higher after previous infection: median (IQR) >21 days post first Pfizer–BioNTech 14 604 (7644–22 291) AU/mL versus 1028 (564–1985) AU/mL without prior infection (p < 0.001). Oxford–AstraZeneca vaccine recipients had lower readings post first dose than Pfizer–BioNTech recipients, with and without previous infection, 10 095 (5354–17 096) and 435 (203–962) AU/mL respectively (both p < 0.001 versus Pfizer–BioNTech). Antibody responses >21 days post second Pfizer vaccination in those not previously infected, 10 058 (6408–15 582) AU/mL, were similar to those after prior infection followed by one vaccine dose. Conclusions: SARS-CoV-2 vaccination leads to detectable anti-spike antibodies in nearly all adult HCWs. Whether differences in response impact vaccine efficacy needs further study.